JACEE long duration balloon flights - Burnett, T.; Iwai, J.; Lord, J.J.; Strausz, S.; Wilkes, R.J. (Washington Univ., Seattle, WA (USA)); Dake, S.; Oda, H. (Kobe Univ. (Japan)); Miyamura, O. (Osaka Univ. (Japan)); Fuki, M. (Matsusho Gakuen Junior Coll., Matsumoto (Japan)); Jones, W.V. (National Aeronautics and Space Administration, Washington, DC (USA)); Gregory, J.; Hayashi, T.; et al. (Washington Univ., Seattle, WA (USA), 1989)
JACEE balloon-borne emulsion chamber detectors are used to observe the spectra and interactions of cosmic ray protons and nuclei in the energy range 1-100A TeV. Experience with long duration mid-latitude balloon flights and characteristics of the detector system that make it ideal for planned Antarctic balloon flights are discussed. 5 refs., 2 figs.